Technology choice between the principal and the agent in an evolutionary context - James Mora, Jhon (Estudios Económicos de El Colegio de México, 1998)
This paper discusses the necessary conditions for principal and agent contract in an evolutionary interactive context and how a specific technology prevails. The resulting stability condition is an Evolutionarily Stable Strategy, ESS, in the Maynard Smith tradition. When productivity is greater or equal to one arises a ESS in a particular technology and when productivity is less than one the only way to explain why a particular technology prevails is by means of a convention.